From 18- to 20-electron ferrocene derivatives via ligand coordination - Satoshi Takebayashi; Jama Ariai; Sergey V. Kartashov; Robert R. Fayzullin; Tomoko Onoue; Ko Mibu; Hyung-Been Kang; Noriko Ishizu (Nature Communications)
Abstract The 18-electron rule is a fundamental rule in coordination chemistry on which several revolutionary discoveries in catalysis and materials science are founded. This rule has classes of exceptions; however, it is widely taught and accepted that diamagnetic 18-electron complexes do not coordinate to a ligand to form a 20-electron complex even as a reaction intermediate. Here, based on tunable ligand design, we report the formation of 20-electron ferrocene derivatives through reversible nitrogen coordination to 18-electron analogs. Through theoretical studies, we have elucidated key features that enabled this coordination chemistry and how the nitrogen coordination shifts the metal−ligand bonding characters. These 20-electron ferrocene derivatives exhibit reversible FeII/FeIII/FeIV redox chemistry under previously unattainable, mild conditions. This work highlights the previously unknown coordination chemistry of diamagnetic 18-electron complexes, which underlies the foundation for future innovations in a range of synthetic chemistry.